(untitled) (Journal of Natural Language and Linguistics, 2024)
The debate over the role of the first language (L1) in English as a Foreign Language (EFL) or English as a Second Language (ESL) classrooms has persisted for decades. It began in the late 1970s and early 1980s, a period during which the use of the native language in language learning settings was permitted. Numerous researchers and educators have investigated the impact of using the mother tongue in EFL/ESL teaching environments, resulting in a wide range of perspectives. Some scholars view the use of the first language (L1) in the EFL classroom as beneficial, while others contend it hinders the learning process. Meanwhile, another group debates the extent to which L1 should be utilized in EFL settings. This research aimed to explore “ A Study on Afghan EFL University Teachers’ Views and Believes on Using Persian in English Language classes” within the Afghan context. A 5-point Likert scale questionnaire was used to collect responses from 20 teachers across 13 universities in Afghanistan. The results showed that the participants supported the careful application of Persian for teaching and learning new vocabulary, clarifying grammar, offering explanations when students fail to comprehend English, detailing complex instructions, elucidating the distinctions between Persian and English rules, and believed that employing Persian enables students to grasp the teachers’ instructions more clearly.